2020
DOI: 10.3390/molecules25225412
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Filtration on Physical and Chemical Properties of Osmo-Dehydrated Material

Abstract: Osmotic dehydration (OD) performed in concentrated fruit juices used as osmotic solution (OS) comes with some limitations resulting from the material cell structure and is not entirely recognized at the moment. Filtration of the juice could provide some insight into the phenomena occurring throughout the OD. Therefore, the main aim of the study was to recognize the mechanism of selective penetration during OD and evaluate the effect of filtration on physical and chemical properties of osmo-dehydrated material.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
(72 reference statements)
2
8
0
Order By: Relevance
“…However, samples treated by NF OS exhibited lower values of CA than in the case of 0.2 OS, which can be due to the size of the particles taking part in the process when filtrated solution was applied. This is consistent with the previous studies by Masztalerz et al [ 15 ], who reported significantly higher antioxidant activity of dehydrated apples when filtrated osmotic solution was applied.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…However, samples treated by NF OS exhibited lower values of CA than in the case of 0.2 OS, which can be due to the size of the particles taking part in the process when filtrated solution was applied. This is consistent with the previous studies by Masztalerz et al [ 15 ], who reported significantly higher antioxidant activity of dehydrated apples when filtrated osmotic solution was applied.…”
Section: Resultssupporting
confidence: 94%
“…Solid gain (SG), water loss (WL) as well as the water loss to solid gain ratio (WL/SG) and specific energy consumption during drying ( E ODw and E ODm ) are presented in Table 1 . Preliminary studies and a literature review revealed that the most intense mass exchange occurs at the beginning of the process, and therefore, osmotic dehydration was carried out for 30 min [ 15 ]. Due to the application of heterogenic concentrated chokeberry juice with the addition of mint infusion, osmotic solutions were filtrated to remove high molecular weight compounds that could disrupt the mass transfer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the factors influencing the chemical composition during OD is filtration of OS. In the studies by Masztalerz, Figiel, et al (2020) and Masztalerz, Lech, et al (2020) it was found that even though filtration of the concentrated chokeberry juice used as OS had little influence on the drying kinetics it affected total phenolic content and antioxidant activity of the material. Whereas Lech et al (2017) reported that the size of the particles in OS affected polyphenolic content and antioxidant capacity of OSs.…”
Section: Introductionmentioning
confidence: 97%